The rootstock genotype shapes the diversity of pecan (Carya illinoinensis) rhizosphere microbial community - Ren, Wei; Zhang, Lu; Tondre, Braden; Wang, Xinwang; Xu, Tingying (Frontiers in Microbiology, 2024)
Pecans (Carya illinoinensis), one of the most valuable native North American nut crops, are commonly propagated through grafting to preserve the desired characteristics from parent trees. Since successful cultivation of pecan trees relies on the interplay among scion varieties, rootstocks, and soil conditions, this study delved into the microbial abundance and diversity in soils and roots of southern (87MX5-1.7) and northern (Peruque) rootstocks in a rootstock test orchard, both grafted with the 'Pawnee' scion cultivar in the USDA ARS Pecan Breeding program. The bacterial 16S ribosomal RNA and fungal ITS were amplified from both roots and rhizosphere soils of the two 10year-grafted trees and then sequenced and annotated into trophic and nutrient-related groups to characterize the rhizosphere microbiota. The results showed Peruque roots having a higher relative abundance of saprotroph fungi, while 87MX5-1.7 exhibited higher levels of symbiotroph fungi and nitrogen fixation-related bacteria. Among them, the presence of symbiotroph fungi, particularly ectomycorrhizal fungi, notably differed between these two rootstocks, with a significantly higher presence observed in the root of 87MX5-1.7 compared to Peruque. This variation likely leads to divergent pathways of nutrient translocation: Peruque was in favor of multiple fungi (Russula and Inocybe) to gain nutrition, while 87MX5-1.7 preferred a specific domain of fungi (Tuber) and nitrogen fixation-related bacteria (Bradyrhizobia) to form beneficial symbiosis. Moreover, the presence of pathogens suggested a potential risk of Fusarium patch and snow molds in 87MX5-1.7, while canker and black foot disease pose threats in Peruque. The findings of this study suggest rootstocks from different origins shape rhizosphere microbes differently, affecting nutrient uptake and potentially nut yield. Exploring rootstock-microbe combinations could provide insights into optimizing scion growth and ultimately increasing nut yield. By understanding how different rootstock-microbe interactions influence pecan tree development, growers can strategically select combinations that promote symbiotic relationships beneficial for nutrient uptake, disease resistance, and overall tree vigor.